Risk of gynecological cancers in cholecystectomized women: a large nationwide cohort study - Kharazmi, Elham; Sundquist, Kristina; Sundquist, Jan; Fallah, Mahdi; Lorenzo Bermejo, Justo (Cancers, 2022)
Background: Gallstones affect women more frequently than men, and symptomatic gallstones are increasingly treated with surgical removal of the gallbladder (cholecystectomy). Breast, endometrial, and ovarian cancer share several risk factors with gallstones, including overweight, obesity, and exposure to female sex hormones. We intended to assess the association between cholecystectomy and female cancer risk, which has not been comprehensively investigated. Methods: We investigated the risk of female cancers after cholecystectomy leveraging the Swedish Cancer, Population, Patient, and Death registries. Standardized incidence ratios (SIRs) adjusted for age, calendar period, socioeconomic status, and residential area were used to compare cancer risk in cholecystectomized and non-cholecystectomized women. Results: During a median follow-up of 11 years, 325,106 cholecystectomized women developed 10,431 primary breast, 2888 endometrial, 1577 ovarian, and 705 cervical cancers. The risk of ovarian cancer was increased by 35% (95% confidence interval (CI) 2% to 77%) in the first 6 months after cholecystectomy. The exclusion of cancers diagnosed in the first 6 months still resulted in an increased risk of endometrial (19%, 95%CI 14% to 23%) and breast (5%, 95%CI 3% to 7%) cancer, especially in women cholecystectomized after age 50 years. By contrast, cholecystectomized women showed decreased risks of cervical (−13%, 95%CI −20% to −7%) and ovarian (−6%, 95%CI −10% to −1%) cancer. Conclusions: The risk of ovarian cancer increased by 35% in a just short period of time (6 months) following the surgery. Therefore, it is worth ruling out ovarian cancer before cholecystectomy. Women undergoing cholecystectomy showed an increased risk of breast and endometrial cancer up to 30 years after surgery. Further evaluation of the association between gallstones or gallbladder removal on female cancer risk would allow for the assessment of the need to intensify cancer screening in cholecystectomized women.
Dieser Artikel gehört zum Sonderheft "Gynaecological cancer and surgery: current practice, novel technologies and future developments"
Gesehen am 12.06.2022